‘This Is the Table Before the Lord’: Visualisations of Tables and Loaves in Lurianic Prayerbooks - Koch, Patrick Benjamin (manuscript cultures, 2025)
A notable feature of kabbalistic prayerbooks is their high textual density. What is also noteworthy is that this texture of different materials is very rarely, if ever, accompanied by schematic or pictorial illustrations. In the manuscripts and printed books that do contain them, illustrations are mostly used to support the text, emphasising and structuring its content. For example, words may be arranged in a particular configuration, such as the shape of the seven-branched candelabrum or menorah. This form of presentation distinguishes the text from its surrounding context and functions as a stimulus for contemplation and reflection.